2014
DOI: 10.3329/bjas.v43i1.19382
|View full text |Cite
|
Sign up to set email alerts
|

Present status of rearing backyard poultry in selected areas of Mymensingh district

Abstract: This study was conducted in Boyra and Sutiakhali villages under Sadar upazila of Mymensingh district to know the present status of backyard poultry production system. The survey data were collected from 40 randomly selected farmers having 20 from each village by interviewing them. The data were then analyzed statistically. All the selected farmers reared deshi chicken and about 54% of them reared deshi duck only. It was also found that highest proportion (75%) of farmers reared both chicken and duck together, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 8 publications
9
28
0
Order By: Relevance
“…Haringhata Black was the fastest (173 days) to reach sexual maturity among four breeds and that was found to be similar to that of local non-descript hens of Bangladesh as reported by Alam et al, (2014). The differences in attaining sexual maturity might be due to the genetic differences among the four groups of birds.…”
Section: Fig1 Body Weight Of Vanaraja Poultrysupporting
confidence: 78%
See 1 more Smart Citation
“…Haringhata Black was the fastest (173 days) to reach sexual maturity among four breeds and that was found to be similar to that of local non-descript hens of Bangladesh as reported by Alam et al, (2014). The differences in attaining sexual maturity might be due to the genetic differences among the four groups of birds.…”
Section: Fig1 Body Weight Of Vanaraja Poultrysupporting
confidence: 78%
“…Hens from Haringhata Black breed showed slowest growth that is common in indigenous lines. Hassen et al, (2006) and Alam et al, (2014) reported similar slow growth pattern of adult non-descript local hens in Ethiopia and Bangladesh respectively. Thakur et al, (2006) suggested that famous Kadaknath breed reared under tribal villages in central India exhibited similar growth pattern like Haringhata Black breed.…”
Section: Resultsmentioning
confidence: 88%
“…In another study in Ethiopia, a lower average flock size (4.1) was detected (Sambo et al, 2015). In other countries, such as in Bangladesh and Belgium, the mean flock size of small holdings of poultry was observed to be less than 11 (Alam et al, 2014;Van Steenwinkel et al, 2011). In a study in some districts of West Bengal (India), such as Jalpaiguri, Dinajpur, West Medinipur, Howrah, and South 24 Parganas, the average flock size was observed as 20-25 (Samanta et al, 2014b).…”
Section: Management Practices In Rural Backyard Farmingmentioning
confidence: 89%
“…In Bangladesh, most of the farmers (55%) keep the birds within their houses, and others keep them in a coop in the front yard. The coop is made of soil or wood and it has a tin shade (Alam et al, 2014;Sultana et al, 2012a). The majority of the farmers prefer to keep the birds on a wooden perch constructed inside their own houses in Ethiopia (Yemane et al, 2013).…”
Section: Management Practices In Rural Backyard Farmingmentioning
confidence: 99%
“…The remarkably low cost of backyard poultry raising drives this high return on investment. Half of the households did not have poultry shed and the other half spent very small amount as backyard poultry sheds in Bangladesh are usually made of locally available materials, such as clay, mud brick, bamboo, broken tin, straw or wood (Sumy et al., ; Alam et al., ). Investment for feed was also minimal, since poultry scavenged freely for feed.…”
Section: Discussionmentioning
confidence: 99%